Patrick Melrose [videorecording (DVD)] - Cumberbatch, Benedict, 1976-; Leigh, Jennifer Jason, 1962-; Weaving, Hugo, 1960-; Maltz, Sebastian; Danner, Blythe; St. Aubyn, Edward, 1960- (Acorn, 2019)
Chronicling the hilarious highs and devastating lows of his tumultuous life, this blackly humorous drama follows Patrick from his childhood trauma at the hands of an abusive father and neglectful mother, to the peak of his heroin addiction, and his attempts to stay sober and support his family.